Verona Coding Definitions of Emotional Sequences (VR-CoDES): Conceptual framework and future directions. Issue 12 (December 2017) - Piccolo, Lidia Del; Finset, Arnstein; Mellblom, Anneli V.; Figueiredo-Braga, Margarida; Korsvold, Live; Zhou, Yuefang; Zimmermann, Christa; Humphris, Gerald
Highlights: VR-CoDES is rooted in patient-centered, biopsychosocial and functional approach to emotion. Emotional communication should be analysed in terms of ongoing sequences of talk. Emotions are often expressed as vague cues and require a specific definition to be identified. Explicitness and provision of space are the two main VR-CoDES dimensions in clinician response. Results from research on VR-CoDES may help raise awareness of emotional sequences. Abstract: Objective: To discuss the theoretical and empirical framework of VR-CoDES and potential future direction in research based on the coding system. Methods: The paper is based on selective review of papers relevant to the construction and application of VR-CoDES. Results: VR-CoDES system is rooted in patient-centered and biopsychosocial model of healthcare consultations and on a functional approach to emotion theory. According to the VR-CoDES, emotional interaction is studied in terms of sequences consisting of an eliciting event, an emotional expression by the patient and the immediate response by the clinician. The rationale for the emphasis on sequences, on detailed classification of cues and concerns, and on the choices of explicit vs. non-explicit responses and providing vs. reducing room for further disclosure, as basic categories of the clinician responses, is described. Conclusions: Results from research on VR-CoDES may help raise awareness of emotional sequences. Future directions in applying VR-CoDES in research may include studies on predicting patient and clinician behavior within the consultation, qualitative analyses of longer sequences including several VR-CoDES triads, and studies of effects of emotional communication on health outcomes. Practice implications: VR-CoDES may be applied to develop interventions to promote good handling of patients' emotions in healthcare encounters.